الأسطورة وتمثلاتها في العصر العباسي [Legendary and its representations in Abbasid era] - Elsayed Mohamed Salem, Salem Elawadi; Mohamed Fathy, Mohamed Abdelgelil; Sharif, Uwidhah (2020)
Literature is a form of supreme human expression; it is the most insignificant way reflecting the ideas and culture of the peoples and nations. Literature in the Abbasid era reached its glory and grandeur; which resulted in a huge and the majestic heritage of a time when its civilization has flourished more than any other civilization before that time, so it was called the Golden Age. Cultural mixing in the Abbasid era caused a complication of literary fantasy forms; hence, scholars and writers innovated new ways resulted in renovation of fantasy and legend. The books of Abbasid era were full of tales and legends which characterized by literary maturity; therefore, this study aims to shed light on the highness and glory of literary arts in Abbasid era and discussing the concept of legendary in terms of language and terminology, and illustrating its patterns in the Arab heritage in general and in the Abbasid era in particular in detail. The importance of this study lies in its focusing on the cumulative knowledge and information through shedding light on legendary in that era, taking samples from the first literary heritage books which highlighted that literary narrative art, depending entirely on descriptive analytical approach.